2020
DOI: 10.1002/ange.202000290
|View full text |Cite
|
Sign up to set email alerts
|

A Chiral Thermochromic Ferroelastic with Seven Physical Channel Switches

Abstract: Switchable materials play an invaluable role in signal processing and encryption of smart devices. The development of multifunctional materials that exhibit switching characteristics in multiple physical channels has attracted widespread attention. Now, two chiral thermochromic ferroelastic crystals (S‐CTA)2CuCl4 and (R‐CTA)2CuCl4 (CTA=3‐chloro‐2‐hydroxypropyltrimethylammonium) have been prepared with switchable properties in dielectricity, conductivity, second harmonic generation (SHG), piezoelectricity, ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Based on this, a significant number of applications in piezoelectric sensors, mechanical switches, shape memory, templating electronic nanostructures and superelasticity make ferroelastic a hot topic in materials science in recent years. [2][3][4][5][6] Moreover, on account of the close relationship between ferroelectricity and ferromagnetism, a good understanding of the ferroelastic properties is crucial to research on ferroelectricity, ferromagnetism and multiferroic materials, including design and switching behavior about them, so to find ferroslastics is quite necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, a significant number of applications in piezoelectric sensors, mechanical switches, shape memory, templating electronic nanostructures and superelasticity make ferroelastic a hot topic in materials science in recent years. [2][3][4][5][6] Moreover, on account of the close relationship between ferroelectricity and ferromagnetism, a good understanding of the ferroelastic properties is crucial to research on ferroelectricity, ferromagnetism and multiferroic materials, including design and switching behavior about them, so to find ferroslastics is quite necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Mercier et al 13 first reported the transformation-induced NLO switchable phenomenon in a molecular-based compound, [{H 3 N(CH 2 ) 2 SS(CH 2 ) 2 NH 3 }PbI 5 ]•H 3 O. Subsequently, a series of molecular-based NLO switchable materials were discovered, such as [α-(H 3 N(CH 2 ) 2 S-S(CH 2 ) 2 NH 3 )BiI 5 , 14 (Hdabco + )(CF 3 COO − ), 15 bis(imidazolium) L -tartrate, 16,17 2-(hydroxymethyl)-2-nitro-1,3-propanediol, 18 (C 4 H 10 N)(CdCl 3 ), 19 dipropylammonium trichloroacetate, 20 (R-CTA) 2 CuCl 4 , 21 and (S-CTA) 2 CuCl 4 . 21 However, despite excellent NLO switchable performance, their bandgaps are relatively narrow on account of π-conjugated electrons, d-d or f-f transition, such as [α-(H 3 N(CH 2 ) 2 S-S(CH 2 ) 2 NH 3 ]BiI 5 (∼1.84 eV), 14 bis(imidazolium) L -tartrate (∼5.21 eV), 17 and dipropylammonium trichloroacetate (∼3.82 eV).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Fig. 3d shows the comparison diagram of T p and the decomposition temperature of molecular hybrid ferroelastics reported at present ((pyrrolidinium) 3 [Sb 2 Cl 9 ], 29 (H 2 NNH 3 ) 3 CdBr 5 , 30 (S-CTA) 2 CuCl 4 , 31 [Et 3 P(CH 2 ) 2 F][Mn(dca) 3 ], 32 (R3HP) 2 RbBiBr 6 , 33 [CPtmp][Cd(SCN) 3 ], 34 [DMEA]PbBr 3 , 35 37 [BFDA]PbBr 3 , 38 (TMTB)-CdCl 3 , 39 (H 2 hpz)[K(BF 4 ) 3 ], 19 and [(R)/(S)-PEDA]PbI 4 40 ), from which it can be seen that compound 2 constructed by precise molecular design has both a high T p and an ultrahigh decomposition temperature, even beyond those of the all-inorganic ferroelastic BaTiO 3 (393 K), 41 and this feature makes it a superior multifunctional switching material for practical application. Then we simply characterized the optical properties of such a multifunctional switching material in Fig.…”
Section: Resultsmentioning
confidence: 97%